A Method for Using Cell-Penetrating Peptides for Loading Plasmid DNA into Secreted Extracellular Vesicles - Jekaterina Nebogatova; Heleri Heike Härk; Anett Puskar; Ly Porosk; Paolo Guazzi; Moataz Dowaidar; Ülo Langel; Kaido Kurrikoff (Biomolecules, 2023)
The low bioavailability and high toxicity of plasmid DNA (pDNA)-based therapeutics pose challenges for their in vivo application. Extracellular vesicles (EVs) have great potential to overcome these limitations, as they are biocompatible native cargo carriers. Various methods for loading pDNA into EVs, including electroporation, sonication, and co-incubation, have been previously investigated, but their success has been questionable. In this study, we report a unique method for loading EVs with pDNA through transient transfection using cell-penetrating peptides (CPPs). With this method, we found a 104-fold increase in the expression levels of the luciferase reporter protein in recipient cells compared to the untreated cells. These data point to the high transfection efficacy and bioavailability of the delivered encapsulated nucleic acid. Furthermore, the in vivo experimental data indicate that the use of pDNA-loaded EVs as native delivery vehicles reduces the toxic effects associated with traditional nucleic acid (NA) delivery and treatment.